2013
DOI: 10.1007/s00232-013-9554-7
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Composition and Electric Charge in Healthy and Cancerous Parts of Human Kidneys

Abstract: Phospholipids are ubiquitous in nature and are essential for the lipid bilayer of cell membranes. Their structural and functional properties are pivotal for the survival of the cell. In this study the phospholipids of healthy and cancerous human renal tissues from the same patients are compared with special reference to the electric charge of the membrane. A simple and highly effective normal-phase method is described for analyzing phospholipids content. This work is focused on changes of phospholipids content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
2
30
0
Order By: Relevance
“…Our previous experiments demonstrated that the cell membrane and the function are modified during cancer transformation. It is reflected by changes in the amount of phospholipids of human renal cell membrane [1]. The results of our research confirm the increase in the levels of phospholipids of renal cancer cell membrane relative to the unmodified cells (Figure 3).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our previous experiments demonstrated that the cell membrane and the function are modified during cancer transformation. It is reflected by changes in the amount of phospholipids of human renal cell membrane [1]. The results of our research confirm the increase in the levels of phospholipids of renal cancer cell membrane relative to the unmodified cells (Figure 3).…”
Section: Discussionsupporting
confidence: 84%
“…portant properties of a biological membrane are its electric charge and its potential drop between the membrane and surrounding solution. Electric properties of the membrane are determined by acid-base and complex formation equilibria of membrane and solution components [1]. Most membrane components-phospholipids and proteins-are involved in those equilibria.…”
mentioning
confidence: 99%
“…[10][11][12] Moreover, there have been no studies comprehensively evaluating anionic lipids using clinical RCC samples. [10][11][12] A MALDI matrix is selective for ionization of certain molecule groups. Our DHB/CHCA binary matrix-based tissue MALDI-MS analysis is optimized for charged lipids, not for neutral lipids such as TAG.…”
Section: Resultsmentioning
confidence: 99%
“…Our study demonstrates that profiling of lipid other than TAGs may be useful for distinguishing RCC tissue from normal tissue samples and for classifying RCC according to its histology. There have been several studies evaluating the lipid profiles of RCC, but previous studies are limited by small sample size . Moreover, there have been no studies comprehensively evaluating anionic lipids using clinical RCC samples …”
Section: Discussionmentioning
confidence: 99%
“…Evidence has accrued that PC, the major phospholipid component of eukaryotic membranes, contributes to both proliferative growth and programmed cell death. On the one hand, the PC content was shown to increase with cell transformation and tumor progression (35)(36)(37)(38). However, on the other hand, PC…”
Section: Ohoa Is Not a Sms Activatormentioning
confidence: 99%